Inflammatory disorders mimicking periprosthetic joint infections may result in false-positive α-defensin. (November 2018) - Plate, A.; Stadler, L.; Sutter, R.; Anagnostopoulos, A.; Frustaci, D.; Zbinden, R.; Fucentese, S.F.; Zinkernagel, A.S.; Zingg, P.O.; Achermann, Y.
Abstract: Objectives: The antimicrobial peptide α-defensin has recently been introduced as a potential 'single' biomarker with a high sensitivity and specificity for the preoperative diagnosis of periprosthetic joint infections (PJIs). However, most studies assessed the benefits of the test with exclusion of patients with rheumatic diseases. We aimed to evaluate the α-defensin test in a cohort study without exclusion of people with inflammatory diseases. Methods: Between June 2016 and June 2017, we prospectively included cases with a suspected PJI and an available lateral flow test α-defensin (Synovasure ® ) in synovial fluid. We compared the test result to the diagnostic criteria for PJIs published by an International Consensus Group in 2013. Results: We included 109 cases (49 hips, 60 knees) in which preoperative α-defensin tests had been performed. Among these, 20 PJIs (16 hips, four knees) were diagnosed. Preoperative α-defensin tests were positive in 25 cases (22.9%) with a test sensitivity and specificity of 90% and 92.1% (95% CI 68.3%–98.8% and 84.5%–96.8%, respectively), and a high negative predictive value of 97.6% (95% CI 91.7%–99.4%). We interpreted seven α-defensin tests as false positive, mainly in cases with inflammatory rheumatic diseases, including crystal deposition diseases. Conclusions: A negative synovial α-defensin test can reliably rule out a PJI. However, the test can be false positive in conjunction with an underlying non-infectious inflammatory disease. We therefore propose to use the α-defensin test only in combination with Musculoskeletal Infection Society criteria and assessment for crystals in synovial aspirates.